LB15. SER-109, an Investigational Microbiome Therapeutic, Reduces Abundance of Antimicrobial Resistance Genes in Patients with Recurrent Clostridioides difficile Infection (rCDI) after Standard-of-Care Antibiotics. (4th December 2021) - Straub, Timothy J; Diao, Liyang; Ford, Christopher; Sims, Matthew; Louie, Thomas J; Berenson, Charles; Kraft, Colleen S; Cohen, Stuart H; Cohen, Stuart H; Paskovaty, Alla; Lombardo, Mary-Jane; McGovern, Barbara; et al.
Abstract: Background: The gastrointestinal microbiota is the first line of defense against colonization with antimicrobial resistant (AR) bacteria, particularly in vulnerable hosts with frequent antibiotic exposure. In a double-blind Phase 3 trial of rCDI patients, SER-109, an orally formulated consortia of purified Firmicutes spores, was superior to placebo in reducing CDI recurrence at week 8 post clinical resolution on standard-of-care (SoC) antibiotics. Overall recurrence rates were lower in SER-109 vs placebo (12.4% vs 39.8%, respectively) relative risk, 0.32 [95% CI, 0.18–0.58; p< 0.001 for RR< 1.0; p< 0.001 for RR< 0.833]. This is a post-hoc analysis examining the impact of SER-109 on antimicrobial resistance genes (ARGs) abundance in the intestinal microbiota compared to placebo. Methods: Subjects with rCDI received SoC antibiotics, then were randomized 1:1 to SER-109 or placebo at baseline. Of 182 subjects, 140 who had paired stool samples at baseline and 1-week post-treatment were included in this analysis. ARG abundances and taxonomic profiles were generated from whole metagenomic shotgun sequencing. t -tests were used to compare changes in ARG abundance from baseline; mixed linear models were used to associate ARG and taxon abundances across time points. Results: ARG abundance was reduced overall by week 1, with a significantly greater decrease in SER-109 subjects vs. placebo at week 1 (Fig. 1). Proteobacteria relative abundance were positively correlated with ARG abundance across all samples (Fig. 2), with the Enterobacteriaceae family associated with the abundance of 95 ARGs (all p < 0.05). Enterococcaceae relative abundance was associated with glycopeptide AR abundance (p < 0.001). At week 1, Proteobacteria relative abundance was significantly decreased from baseline in SER-109 subjects vs. placebo (p < 0.001). Enterobacteriaceae and Enterococcaceae relative abundances were also decreased from baseline in SER-109 subjects vs. placebo (p < 0.001 and p = 0.007, respectively). Figure 1. Significant reduction in ARG abundance at week 1 from baseline in SER-109 treatment compared to placebo. Figure 2. Total ARG abundance is associated with the relative abundance of Proteobacteria in SER-109 and placebo subjects at baseline and week 1. Conclusion: SER-109 was associated with significantly greater reduction of ARGs and AR bacteria abundances compared to placebo at 1 week post treatment. These findings support a potential role of microbiome therapeutics in rapid decolonization of AR bacteria with implications for infection prevention. Disclosures: Timothy J. Straub, MS, Seres Therapeutics (Employee) Liyang Diao, PhD, Seres Therapeutics (Employee) Christopher Ford, PhD, Seres Therapeutics (Employee, Shareholder) Matthew Sims, MD, PhD, Astra Zeneca (Independent Contractor)Diasorin Molecular (Independent Contractor)Epigenomics Inc (Independent Contractor)Finch (Independent Contractor)Genentech (Independent Contractor)Janssen Pharmaceuticals NV (Independent Contractor)Kinevant Sciences gmBH (Independent Contractor)Leonard-Meron Biosciences (Independent Contractor)Merck and Co (Independent Contractor)OpGen (Independent Contractor)Prenosis (Independent Contractor)Regeneron Pharmaceuticals Inc (Independent Contractor)Seres Therapeutics Inc (Independent Contractor)Shire (Independent Contractor)Summit Therapeutics (Independent Contractor) Thomas J. Louie, MD, Artugen (Advisor or Review Panel member)Crestone (Consultant, Grant/Research Support)Da Volterra (Advisor or Review Panel member)Finch Therapeutics (Grant/Research Support, Advisor or Review Panel member)MGB Biopharma (Grant/Research Support, Advisor or Review Panel member)Rebiotix (Consultant, Grant/Research Support)Seres Therapeutics (Consultant, Grant/Research Support)Summit PLC (Grant/Research Support)Vedanta (Grant/Research Support, Advisor or Review Panel member) Colleen S. Kraft, MD, MSc, Rebiotix (Individual(s) Involved: Self): Advisor or Review Panel member Stuart H. Cohen, MD, Seres (Research Grant or Support) Stuart H. Cohen, MD, Nothing to disclose Mary-Jane Lombardo, PhD, Seres Therapeutics (Employee, Shareholder) Barbara McGovern, MD, Seres Therapeutics (Employee, Shareholder) Lisa von Moltke, MD, Seres Therapeutics (Employee, Shareholder) Matt Henn, PhD, Seres Therapeutics (Employee, Shareholder)